ANALISIS PRODUKTIVITAS USAHATANI PADI SAWAH DENGAN MENGGUNAKAN TRAKTOR TANGAN DAN CARA KONVENSIONAL DI KABUPATEN REJANG LEBONG - Silamat, Edi; Yuwana, Yuwana; Yuliarso, M. Zulkarnain (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The aims of this research are to (1) determine factors that affect rice farmers decision to use hand tractor or not (conventional), (2) analyze the productivity of rice using hand tractors and conventional technique. (3) Calculate the income of rice farmers that used tractors and conventional. The number of samples taken were 41 rice farmers who used hand tractors in the village of Rimbo Recap and the ones who used conventional technique 29 persons in Watas Marga village. The systems of farming was the same both in Watas Marga village and in Rimbo Recap. Sampling was conducted by interview using questionnaire to collect primer data and secunder data. The method of research was survey using the formula Slovin. The result of study concluded that the land space and perception of labor significantly affected the farmer’s decision to use the hand tractors, while the perception of farmers on hand tractors did not affect significantly on the farmer’s decision to use hand tractors in agricultural land preparation. Factors that affected the productivity were seeds 4.569 t count > t table of 2.564 and labor 8.936 t count > t table of 2.464t count > t table 2.042 and labor 8.936 t count > t table of 2.464 with 99% confidence level. Insectiside had significant effect on productivity of rice at 95% level. The value of t count was 2.479 > t table (2.042). T test had a negative value. Dummy showed decrease in productivity by 0.2077% if the farmer did not use a hand tractor. Incomes of farmers who used both tractors and conventional technique showed no significant difference. Income of farmers who used tractors was Rp. 9.014.727/MT or Rp. 11. 302.316/Ha and farmers' income whoutilize conventional technique was Rp. 9.041.365/MT or Rp. 11.349.945/Ha. The calculation results based on different incomes concluded that change in rice farming systems did not significantly effect on income benefit